2021
DOI: 10.1080/02508060.2021.1885126
|View full text |Cite
|
Sign up to set email alerts
|

Economy-wide assessment of potential long-term impacts of the Grand Ethiopian Renaissance Dam on Sudan

Abstract: The Grand Ethiopian Renaissance Dam (GERD) is expected to double Ethiopia's electricity 14 generation and impact Nile flows to Sudan and Egypt. We analyze some potential economy-wide 15 impacts on Sudan of the -term operation using a computable general equilibrium model 16 and outputs from hydrologic, river system, and crop models. Results show that the expected increase 17 in hydropower generation and the possible expansion of irrigation-area in Sudan due to river flow 18 regulation by the GERD could increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The Grand Ethiopian Renaissance Dam (GERD) located on the Blue Nile River in Ethiopia, promises a massive reservoir, which has been expanding according to a series of satellite images, with a spatial extent of about 1763.3 km 2 and capacity of more than 70 billion cubic meters of water [1,2]. The filling process and its implications on the downstream river hydrology has been recently monitored using Sentinel-1 Synthetic Aperture Radar (SAR) and Sentinel-2 optical imagery [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Grand Ethiopian Renaissance Dam (GERD) located on the Blue Nile River in Ethiopia, promises a massive reservoir, which has been expanding according to a series of satellite images, with a spatial extent of about 1763.3 km 2 and capacity of more than 70 billion cubic meters of water [1,2]. The filling process and its implications on the downstream river hydrology has been recently monitored using Sentinel-1 Synthetic Aperture Radar (SAR) and Sentinel-2 optical imagery [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies evaluated transboundary water quality or climate change impacts (Kandulu & Connor, 2017) which was not our focus and thus these were excluded (Amjath-Babu et al, 2019;Burek et al, 2019;Kahil et al, 2019;Kahsay et al, 2019;Paulos, 2019;Teotónio et al, 2020). On the other hand, five papers were rejected as they were not peer-reviewed (Siehlow et al, 2012;Oei & Siehlow, 2014;Siddig et al, 2019;Abdulloev, 2020). The review revealed that some authors published many similar articles on the same river basin.…”
Section: Methodsmentioning
confidence: 99%
“…The initial purpose of the Grand Ethiopian Renaissance Dam (GERD) is to produce from 5 to 6.4 GW hydroelectric power based on different designs (Kansara et al, 2021;Siddig et al, 2020). The latest negotiations between Egypt, Sudan, and Ethiopia that was halted for reaching a dead end in July 2020, which is around the period of filling the dam lake for the first year with 5 BCM (U.S. Department of the Treasury, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is very important to have Environmental and Social Impact Assessment (ESIA) studies for the GERD project, which are required by law and an obligation before a country develops any transboundary project that necessitates it (Morsy et al, 2020). Although it is quite straight forward to expect the various negative impacts of GERD on the environment in Ethiopia and the downstream countries, the magnitude of the effect is not very easy to determine due to multiple and complicated factors affecting them (Wheeler et al, 2020) such as the rainfall and discharge from the GERD during the filling period, how quickly Ethiopia is planning to fill the reservoir, how much Electric power is planned to be extracted from the dam, which depends on the extent of the grid development in Ethiopia (Eldardiry & Hossain, 2021), how building the dam is going to affect Sudan withdrawal (Siddig et al, 2020), the water level in the High Aswan Dam (HAD) reservoir before GERD, and how HAD will be operated during the filling of GERD reservoir. Despite being complicated to measure, the environmental impacts can be a critical factor in the Egyptian Ethiopian negotiations on the GERD.…”
Section: Introductionmentioning
confidence: 99%